Controlling gully erosion: an analysis of land reclamation processes in Chambal Valley, India. Issue 8 (16th November 2016) - Pani, Padmini
ABSTRACT: Programmes for environmental protection and land reclamation have been deeply embedded in local political and social contexts. This article focuses on the effectiveness of such measures to control ravine erosion in the lower Chambal Valley, one of the most degraded regions in India. The study used field observation to see whether the measures had any impact on further gully and ravine formation. The findings suggest that agricultural practices, including those often based on the short-term economic needs of households, lead to inefficient land-use practices, particularly in land-levelled and reclaimed areas.